PostgreSQL server programming : extend PostgreSQL and integrate the database layer into your development framework - Krosing, Hannu (Community experience distilled., 2013)
This practical guide leads you through numerous aspects of working with PostgreSQL. Step by step examples allow you to easily set up and extend PostgreSQL. ""PostgreSQL Server Programming"" is for moderate to advanced PostgreSQL database professionals. To get the best understanding of this book, you should have general experience in writing SQL, a basic idea of query tuning, and some coding experience in a language of your choice.